2021
DOI: 10.3329/ajmbr.v7i2.54996
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status of fisher communities in Dengar beel under Melandah Upazila, Jamalpur, Bangladesh

Abstract: The current study was conducted to evaluate the socio-economic profile of fisher communities in Dengar beel under Melandah Upazila of Jamalpur district, Bangladesh. A total of 45 fishers were surveyed from November 2020 to April 2021. It was found that the family size of 53% of fishers was medium, consisting of 5-6 members. Most of the fisher communities belonged to the age group above 45 years old, represented by 100% Muslim. About 73% of fishers were less educated, 13% primary level, 7% secondary level, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…In this survey, 52.54 % of the families were nuclear, while 47.46 % were joint (Table 1). The results were in agreement with Islam et al (2021b) who found joint family represented for 33% of the total, while a nuclear family represented for 67%. Bappa et al (2014) stated that fishermen surrounding the Marjat Baor in Kaligonj, Jhenidah district, were found to have 44% joint and 56% nuclear families, which is similar to current figures.…”
Section: Socio-demographic Profile Of Fishermensupporting
confidence: 91%
“…In this survey, 52.54 % of the families were nuclear, while 47.46 % were joint (Table 1). The results were in agreement with Islam et al (2021b) who found joint family represented for 33% of the total, while a nuclear family represented for 67%. Bappa et al (2014) stated that fishermen surrounding the Marjat Baor in Kaligonj, Jhenidah district, were found to have 44% joint and 56% nuclear families, which is similar to current figures.…”
Section: Socio-demographic Profile Of Fishermensupporting
confidence: 91%
“…The state of the people's livelihoods serves as an illustration of their current position, lifestyle, and financial situation (Scoones, 2009). However, few studies on socio-economic conditions of fishermen were carried out by Al-Asif and Habib (2018), , Hossain et al (2016), Vaumik et al (2017, Islam et al (2021) and Razeim et al (2017) but all these efforts lack specific information of livelihood like access to organizations, livelihood vulnerabilities and outcomes. Therefore, the present study was undertaken to determine the fish biodiversity status and livelihood of the fishermen of Habullah baor.…”
Section: Introductionmentioning
confidence: 99%
“…The data collected from 4 different sites finally compiled together to get a clear picture regarding socio-economic status of Cox's Bazar district. [8] reported that, for the fishing community of Padma River, Chapai Nawabgonj district majority (72%) of family having 4-6 people. Whereas only 12% of the families consist of just 1-3 members and the rest (16%) has the member more than 6.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, illiterate fishermen also want that their children should be literate and they should have a better life. Islam et al (2021) [8] mentioned that 49% of the fishermen attended below class 5 and only 7% beyond the secondary level at Dengar Beel under Melandah Upazila, Jamalpur. In another study, Islam et al (2017) [9] found that 73% received no education, 13% attained primary education and 7% were at secondary level at Padma River in Chapai Nawabganj district.…”
Section: Educational Statusmentioning
confidence: 99%
See 1 more Smart Citation